Oral Tumors; Clinicopathological Study among Patients Attending ENT Clinic in Baghdad - Muhsen, Hussein J.; AL-Raheem, Yousif . A (AL-Kindy College Medical Journal, 2009)
Background: Oral tumors are one of the most challengingtumors regarding their good prognosis in early diagnosis andvery difficult control in advancing stages.Objectives: To study the prevalence, types and clinicalpresentation of oral tumors in comparison to other orallesions among patients attending ENT clinic.Al-Kindy Col Med J 2008 Vol.5(1) Original Article 11Methods: This study included 534 patients with differentoral complains attending ENT clinics in AI-YarmoukTeaching Hospital, and AI-Kindy Teaching Hospital -Baghdad, in the period from 1st jan1999 till 31th des 2006 (8years interval).Results: The results of this study showed that the prevalenceof malignant lesions was 13.5% (72 out of 534); the malesconstitute 59.7 % of them. Premalignant lesions constituteonly 3.9% (21 out of 534) of patients; the males constitute66.7 % of them. Benign lesions in 8.6% (46 out of 534); themales constitute 69.6 % of them. Other lesions constitute74% (395 out of 534); the males constitute 65.8 % of them.Squamous cell carcinoma is the most common malignanttumor (found in 71% of malignant lesions).Conclusions: Most patients are males and the most commonmanifestation is sore throat. The most common sign ofpresentation is swelling and the most common histologicaltype of malignant tumors is squamous cell carcinoma (71%).These patients usually attend ENT clinic seeking for simpletherapy, we see that it’s the job of the otolaryngologist todiagnose those patients early which has a major influence onprognosi